Application of calcium indium sulfide coated nickel titanate composite photocatalyst in hexavalent chromium reduction
By coating the nickel titanate composite photocatalyst with indium sulfide, the problem of insufficient activity of semiconductor photocatalysts in the prior art under visible light is solved, and efficient reduction of hexavalent chromium is achieved, which significantly improves the treatment efficiency and removal rate.
Patent Information
- Application Number
- CN202411249304.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-09-06
AI Technical Summary
When using the wastewater containing hexavalent chromium, the existing semiconductor photocatalysts have wide band gaps and low visible light utilization, which limits the photocatalytic activity and makes it difficult to effectively reduce hexavalent chromium under visible light.
Indium calcium sulfide coated with nickel titanate composite photocatalyst, by growing indium calcium sulfide nanosheets on the surface of nickel titanate nanorods, forming a heterostructure, enhancing photogenerated charge separation and visible light absorption capacity, and promoting the reduction of hexavalent chromium.
The catalytic activity of visible light is significantly improved, and the efficient reduction of hexavalent chromium is achieved, with a removal rate of 95%, and a reduction rate of 0.036 min-1, achieving efficient and low-cost treatment of chromium heavy metal contaminated water bodies.
Smart Images

Figure CN118767994B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of environmental pollution control, and specifically relates to the application of a calcium indium sulfide-coated nickel titanate composite photocatalyst in the reduction of hexavalent chromium. Background Art
[0002] Compared with traditional chemical reduction, electroreduction and biological reduction methods of hexavalent chromium, semiconductor photocatalytic reduction has high treatment efficiency, simple process, and no secondary pollution. It is a sustainable and environmentally friendly technology for treating hexavalent chromium-containing wastewater. However, most semiconductor photocatalysts have problems such as wide band gap and low visible light utilization. Most of them can only show good photocatalytic activity under ultraviolet light, which limits the application of photocatalytic reagents. Therefore, the development of highly active visible light catalysts is an urgent problem to be solved.
[0003] Therefore, in order to solve the above technical problems, it is necessary to provide a calcium indium sulfide-coated nickel titanate composite photocatalyst, a preparation method and an application thereof.
[0004] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention and should not be regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art. Summary of the invention
[0005] The purpose of the present invention is to provide an application of a calcium indium sulfide-coated nickel titanate composite photocatalyst in the reduction of hexavalent chromium.
[0006] In order to achieve the above object, a technical solution provided by a specific embodiment of the present invention is as follows:
[0007] Application of indium calcium sulfide coated nickel titanate composite photocatalyst in hexavalent chromium reduction, the application is carried out in an aqueous solution system, the catalyst includes nickel titanate nanorods and indium calcium sulfide nanosheets formed on the nickel titanate nanorods;
[0008] The mass ratio of indium calcium sulfide nanosheets to nickel titanate nanorods is (0.5-10):1.
[0009] In one or more embodiments of the present invention, the calcium indium sulfide nanosheets are distributed on the nickel titanate nanorods in a randomly cross-linked form, such as in the form of clusters, such as a honeycomb, etc.
[0010] In one or more embodiments of the present invention, the nickel titanate nanorods have a diameter of 300-400 nanometers and a length of 1-1.5 micrometers.
[0011] In one or more embodiments of the present invention, the specific surface area of the catalyst is 65-75 m 2 / g.
[0012] In one or more embodiments of the present invention, a method for preparing a calcium indium sulfide-coated nickel titanate composite photocatalyst comprises:
[0013] preparing nickel titanate nanorods;
[0014] Disperse the nickel titanate nanorods in a solvent, adjust the pH, add a dispersant, a calcium salt, an indium salt, and a vulcanizing agent, mix them evenly, and then react in a water bath and separate them. Preferably, the solvent is water. Preferably, the dispersant is glycerol. Preferably, the zinc salt is zinc chloride or zinc sulfate. Preferably, the indium salt is hydrated indium nitrate or indium chloride tetrahydrate. Preferably, the vulcanizing agent is thioacetamide.
[0015] In one or more embodiments of the present invention, the molar ratio of calcium salt, indium salt and sulfiding agent is 1:2:(4-8).
[0016] In one or more embodiments of the present invention, the volume ratio of the dispersant to water is (0-0.5):1, excluding 0.
[0017] In one or more embodiments of the present invention, the pH value is: 1-4, excluding the endpoints, preferably 2-3, and more preferably 2.5.
[0018] In one or more embodiments of the present invention, the conditions of the water bath are: temperature of 60-100° C., and time of 1-3 h.
[0019] Specifically, the primary purpose of the present invention is to provide a calcium indium sulfide-coated nickel titanate composite photocatalyst that can promote the separation of photogenerated charges in calcium indium sulfide and enhance the photocatalytic effect.
[0020] The second object of the present invention is to provide a method for preparing the above-mentioned calcium indium sulfide-coated nickel titanate composite photocatalyst.
[0021] The third object of the present invention is to provide an application of the above-mentioned calcium indium sulfide-coated nickel titanate composite photocatalyst.
[0022] Technical solution: In the calcium indium sulfide-coated nickel titanate composite photocatalyst of the present invention, calcium indium sulfide nanosheets are coated on the surface of nickel titanate nanorods, and the mass ratio of calcium indium sulfide to nickel titanate is (0.5-10):1.
[0023] The preparation method of the above-mentioned indium calcium sulfide-coated nickel titanate composite photocatalyst first uses nickel salt, ethylene glycol and tetrabutyl titanate as raw materials, reacts for a period of time, obtains a precursor by liquid phase co-precipitation method, washes, centrifuges and dries to obtain a precursor powder. Further, nickel titanate nanorods are obtained by high-temperature calcination; the nickel titanate nanorods are ultrasonically dispersed in water, the pH value of the solution is adjusted to acidic, a dispersant is added, and then the calcium salt, indium salt and sulfiding agent are evenly mixed, and then heated in a water bath for reaction, and the obtained product is centrifuged, washed and dried to obtain an indium calcium sulfide-coated nickel titanate composite photocatalyst.
[0024] Among them, the mass ratio of the theoretical yield of calcium indium sulfide to the added nickel titanate is (0.5-10):1, so as to ensure that calcium indium sulfide can be coated on the surface of nickel titanate and fully contact with nickel titanate, promote the charge transfer between calcium indium sulfide and nickel titanate, and at the same time increase the contact area between calcium indium sulfide and hexavalent chromium.
[0025] The calcination temperature of the nickel titanate precursor powder is 400-700 °C to ensure that the precursor is fully converted into nickel titanate while avoiding sintering.
[0026] The molar ratio of calcium salt, indium salt and sulfiding agent is 1:2:(4-8) to ensure that the calcium salt, indium salt and sulfiding agent fully react to form calcium indium sulfide.
[0027] The pH value of the dispersed nickel titanate nanorods is greater than 1 and less than 4, preferably 2-3, and more preferably 2.5, to ensure uniform growth of calcium indium sulfide on the surface of nickel titanate and rapid reduction of hexavalent chromium.
[0028] The volume ratio of the dispersant to water is 0-1 / 2:1, excluding 0, to ensure the successful preparation of the indium calcium sulfide-coated nickel titanate composite photocatalyst and its high photocatalytic activity.
[0029] The zinc salt is zinc chloride or zinc sulfate, the indium salt is hydrated indium nitrate or tetrahydrated indium chloride, and the vulcanizing agent is thioacetamide.
[0030] The water bath heating temperature is 60-100°C for 1-3 h, and the reactants react fully to generate indium calcium sulfide nanosheets that are evenly coated on the surface of nickel titanate nanorods.
[0031] Application of the above-mentioned calcium indium sulfide-coated nickel titanate composite photocatalyst in the reduction of hexavalent chromium.
[0032] Principle: The calcium indium sulfide coated nickel titanate composite photocatalyst is to in situ grow calcium indium sulfide nanosheets on the surface of nickel titanate nanorods, which can promote the more uniform dispersion of calcium indium sulfide nanosheets and facilitate the adsorption of hexavalent chromium through more active sites; at the same time, the heterogeneous structure formed by calcium indium sulfide and nickel titanate promotes the carrier migration of the two and inhibits the recombination of photogenerated electrons and holes inside the semiconductor; in addition, in the reduction of hexavalent chromium by the catalyst of the present invention, the photogenerated electrons of nickel titanate and the photogenerated holes of calcium indium sulfide can be recombinated, so that the conduction band electrons of calcium indium sulfide participate in the reduction of hexavalent chromium; the conduction band electrons of calcium indium sulfide can also directly reduce the hexavalent chromium to trivalent chromium, or the hexavalent chromium can be reduced by first reacting with oxygen to generate superoxide ion radicals.
[0033] Beneficial effects: Compared with the prior art, the present invention has the following significant effects: the specific surface area of the indium calcium sulfide-coated nickel titanate composite photocatalyst is large (e.g., it can reach 72.05 m 2 / g; the specific surface area of calcium indium sulfide is 50.84 m 2 / g; the specific surface area of nickel titanate is 40.85 m 2 / g), which enhances the visible light absorption capacity, and at the same time, provides more catalytic reaction sites, promoting the adsorption of hexavalent chromium and calcium indium sulfide; more importantly, calcium indium sulfide and nickel titanate form a heterojunction structure, which promotes the separation of photogenerated electrons and holes in calcium indium sulfide and nickel titanate; the calcium indium sulfide-coated nickel titanate composite photocatalyst exhibits excellent photocatalytic reduction of hexavalent chromium. The present invention uses nickel salt, tetrabutyl titanate, and ethylene glycol as raw materials to prepare a nickel titanate precursor by a liquid phase co-deposition method, and prepares nickel titanate nanorods by calcination; further, nickel titanate, calcium salt, indium salt and thioacetamide are used as raw materials, and water bath heating is used to make calcium indium sulfide nanosheets grow uniformly and coat the surface of nickel titanate nanorods, which promotes the dispersion of calcium indium sulfide nanosheets, enhances visible light absorption, promotes charge separation, and enhances the effect of photocatalytic reduction of hexavalent chromium. In one technical solution, after 80 minutes of visible light irradiation, the catalytic system can achieve a removal rate of 95% for 50 mL of 40 mg / L potassium dichromate solution, and a reduction rate of 0.036 min -1 .
[0034] In summary, compared with the prior art, the application of the calcium indium sulfide-coated nickel titanate composite photocatalyst in the reduction of hexavalent chromium can promote the photogenerated charge separation of calcium indium sulfide, enhance the photocatalytic reduction of hexavalent chromium, and achieve efficient and low-cost treatment of chromium heavy metal contaminated water bodies. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0036] Figure 1 It is the X-ray crystal diffraction spectrum of nickel titanate (NiTiO3) prepared in comparative example 1, calcium indium sulfide (CaIn2S4) prepared in comparative example 2, and calcium indium sulfide-coated nickel titanate composite photocatalyst (CaIn2S4 / NiTiO3) prepared in Example 1, Example 2, and Example 3.
[0037] Figure 2 It is a scanning electron microscope image of calcium indium sulfide, nickel titanate and the calcium indium sulfide-coated nickel titanate composite photocatalyst (CaIn2S4 / NiTiO3 1:1) prepared in Example 1.
[0038] Figure 3 This is the X-ray photoelectron spectrum of the calcium indium sulfide-coated nickel titanate composite photocatalyst prepared in Example 1.
[0039] Figure 4 It is the ultraviolet visible diffuse reflectance spectra of calcium indium sulfide, nickel titanate and the calcium indium sulfide-coated nickel titanate composite photocatalyst prepared in Example 1, Example 2 and Example 3.
[0040] Figure 5 It is the fluorescence emission spectra of calcium indium sulfide, nickel titanate and the calcium indium sulfide-coated nickel titanate composite photocatalyst prepared in Example 1.
[0041] Figure 6 These are the nitrogen adsorption and desorption curves of calcium indium sulfide, nickel titanate, and the calcium indium sulfide-coated nickel titanate composite photocatalyst prepared in Example 1.
[0042] Figure 7 It is a photocatalytic reduction curve of potassium dichromate by calcium indium sulfide-coated nickel titanate composite photocatalyst prepared in Example 1, Example 2, and Example 3, and CaIn2S4 and NiTiO3 prepared in Comparative Examples 1, 2, 3, and 4.
[0043] Figure 8 It is a photocatalytic reduction kinetic curve of potassium dichromate by calcium indium sulfide-coated nickel titanate composite photocatalysts prepared in Example 1, Example 2, and Example 3, and CaIn2S4 and NiTiO3 prepared in Comparative Examples 1, 2, 3, and 4.
[0044] Fig. 9This is a photocatalytic reduction curve of potassium dichromate by the calcium indium sulfide-coated nickel titanate composite photocatalyst prepared in Example 1, Example 16, and Example 17.
[0045] Fig.10 This is a photocatalytic reduction kinetic curve of potassium dichromate by the calcium indium sulfide-coated nickel titanate composite photocatalyst prepared in Example 1, Example 16, and Example 17. DETAILED DESCRIPTION
[0046] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0047] Calcium indium sulfide (CaIn2S4) is a ternary metal sulfide photocatalyst with a narrow band gap, strong visible light response ability, and a relatively negative conduction band potential, which has attracted the attention of scientists. However, the single CaIn2S4 semiconductor has the problem of easy recombination of photogenerated charges like other semiconductors, which limits its practical application. To this end, researchers have adopted methods such as morphology regulation, element doping, and composite with other semiconductors to improve the wide and deep charge separation efficiency of CaIn2S4, thereby improving its photocatalytic activity. For a long time, ternary oxides have been widely used in solid fuel cells, photocatalysis, and sensors. As a typical ternary oxide, nickel titanate (NiTiO3) has the advantages of good visible light response, high catalytic activity, and good stability. In addition, the band gap position of NiTiO3 theoretically matches the band gap of CaIn2S4, which is easy for the circulation of photogenerated carriers. The present invention proposes a preparation method of a calcium indium sulfide-coated nickel titanate composite photocatalyst, and uses it to study the visible light reduction degradation of hexavalent chromium. The composite photocatalyst can make full use of the advantages of CaIn2S4 and NiTiO3, improve the electron transfer efficiency of CaIn2S4, and thus greatly improve the activity of calcium indium sulfide in photocatalytic reduction of hexavalent chromium.
[0048] Example 1
[0049] 5 mL of tetrabutyl titanate and 100 mL of ethylene glycol were mixed, and 2.48 g of nickel acetate tetrahydrate was added after thorough mixing. The reaction was stirred for 1 h, and then a light blue precipitate was obtained. Subsequently, the product was washed and centrifuged three times with deionized water and ethanol solution, and then the product was vacuum dried at 60 °C for 4 h, and finally ground to obtain a precursor powder, which was heat treated at 600 °C for 2 h to obtain nickel titanate nanorods.
[0050] Use a measuring cylinder to measure 32 ml of deionized water, adjust the pH of the solution to 2.5, and then use a measuring cylinder to measure 8 mL of glycerol and add it to the beaker. Stir for 10 min to completely mix the glycerol and water. Use a four-position balance to weigh 1.0 mmol of indium trichloride tetrahydrate (InCl3•4H2O), 0.5 mmol of calcium chloride (CaCl2), 3.0 mmol of thioacetamide (C2H5N S ). Continue stirring for 20 minutes until all the drugs are completely dissolved, accurately weigh the same mass of nickel titanate nanorods according to the theoretical yield of 0.5 mmol indium calcium sulfide and add them to the reaction system (the product is marked as CaIn2S4 / NiTiO3 1:1), continue ultrasonication for 30 minutes, then transfer the solution to a three-necked flask, heat it in a water bath at 80°C and stir for 2 hours to allow it to react fully. After the reaction is completed, take it out and wait for it to cool to room temperature, wash the CaIn2S4 / NiTiO3 1:1 product with deionized water and ethanol, and centrifuge it. Then, the product obtained by centrifugation and washing is vacuum dried at 60°C for 12 hours, ground into powder with a mortar, and finally ground to obtain a CaIn2S4 / NiTiO3 1:1 powder sample.
[0051] Take 1000 μL of 2 g / L K2Cr2O7 mother liquor and add it to the reactor. Add 49 ml of deionized water and stir evenly. Take 4 ml as the reference solution. Then weigh 20 mg of CaIn2S4 / NiTiO3 1:1 powder and put it into the reactor. Stir evenly and perform dark reaction for 30 min. After the dark reaction, take 4 mL of solution into a centrifuge tube. Then turn on the xenon lamp and take 4 mL of the mixed solution into the centrifuge tube every 10 min. Take 8 samples in total and centrifuge them with a centrifuge. Take the supernatant and test the UV-visible absorption spectrum of the hexavalent chromium residual solution with a UV-visible spectrophotometer. Select the absorbance of the K2Cr2O7 solution at the maximum absorption wavelength of 258 nm to obtain the curve of the concentration change of the K2Cr2O7 solution over time, as shown in Figure 1. Figure 7 As shown, the reduction rate of K2Cr2O7 obtained after 80 min of visible light irradiation is 95%. The curve conforms to the first-order kinetic law. The linear fitting is performed by taking the -In(C / C0) value of each reaction time point as the ordinate and the reaction time t as the abscissa to obtain the kinetic curve diagram ( Figure 8 ), the reduction rate of hexavalent chromium was obtained to be 0.036 min -1 .
[0052] Example 2
[0053] 5 mL of tetrabutyl titanate and 100 mL of ethylene glycol were mixed, and 2.48 g of nickel acetate tetrahydrate was added after thorough mixing. The reaction was stirred for 1 h, and then a light blue precipitate was obtained. Subsequently, the product was washed and centrifuged three times with deionized water and ethanol solution, and then the product was vacuum dried at 60 °C for 4 h, and finally ground to obtain a precursor powder, which was heat treated at 600 °C for 2 h to obtain nickel titanate nanorods.
[0054] Use a measuring cylinder to measure 32 ml of deionized water, adjust the pH of the solution to 2.5, and then use a measuring cylinder to measure 8 mL of glycerol and add it to the beaker. Stir for 10 min to completely mix the glycerol and water. Use a four-position balance to weigh 1.0 mmol of indium trichloride tetrahydrate (InCl3•4H2O), 0.5 mmol of calcium chloride (CaCl2), 3.0 mmol of thioacetamide (C2H5N S ). Continue stirring for 20 minutes until all the drugs are completely dissolved, accurately weigh nickel titanate nanorods according to half of the theoretical yield of 0.5 mmol calcium indium sulfide and add them to the reaction system (the product is marked as CaIn2S4 / NiTiO3 1:0.5), continue ultrasonication for 30 minutes, then transfer the solution to a three-necked flask, heat it in a water bath at 80°C and stir for 2 hours to allow it to react fully. After the reaction is completed, take it out and wait for it to cool to room temperature, wash the CaIn2S4 / NiTiO3 1:0.5 product with deionized water and ethanol, and centrifuge it. Then, the product obtained by centrifugation and washing is vacuum dried at 60°C for 12 hours, ground into powder with a mortar, and finally ground to obtain a CaIn2S4 / NiTiO3 1:0.5 powder sample.
[0055] Take 1000 μL of 2 g / L K2Cr2O7 mother solution and add it to the reactor. Add 49 ml of deionized water and stir evenly. Take 4 ml as reference solution. Then weigh 20 mg of CaIn2S4 / NiTiO3 1:0.5 powder and put it into the reactor. Stir evenly and perform dark reaction for 30 min. After the dark reaction, take 4 mL of solution into a centrifuge tube. Then turn on the xenon lamp and take 4 mL of the mixed solution into the centrifuge tube every 10 min. Take 8 samples in total and centrifuge them in a centrifuge. Take the supernatant and test the UV-visible absorption spectrum of the hexavalent chromium residual solution using a UV-visible spectrophotometer. Figure 7 As shown, the reduction rate of K2Cr2O7 obtained after 80 min of visible light irradiation is 92%. The curve conforms to the first-order kinetic law. The linear fitting is performed by taking the -In(C / C0) value of each reaction time point as the ordinate and the reaction time t as the abscissa to obtain the kinetic curve diagram ( Figure 8 ), the reduction rate of hexavalent chromium is 0.029 min -1.
[0056] Example 3
[0057] 5 mL of tetrabutyl titanate and 100 mL of ethylene glycol were mixed, and 2.48 g of nickel acetate tetrahydrate was added after thorough mixing. The reaction was stirred for 1 h, and then a light blue precipitate was obtained. Subsequently, the product was washed and centrifuged three times with deionized water and ethanol solution, and then the product was vacuum dried at 60 °C for 4 h, and finally ground to obtain a precursor powder, which was heat treated at 600 °C for 2 h to obtain nickel titanate nanorods.
[0058] Use a measuring cylinder to measure 32 ml of deionized water, adjust the pH of the solution to 2.5, and then use a measuring cylinder to measure 8 mL of glycerol and add it to the beaker. Stir for 10 min to completely mix the glycerol and water. Use a four-position balance to weigh 1.0 mmol of indium trichloride tetrahydrate (InCl3•4H2O), 0.5 mmol of calcium chloride (CaCl2), 3.0 mmol of thioacetamide (C2H5N S ). Continue stirring for 20 minutes until all the drugs are completely dissolved, accurately weigh nickel titanate nanorods according to 1.5 times the theoretical yield of 0.5 mmol indium calcium sulfide and add them to the reaction system (the product is marked as CaIn2S4 / NiTiO3 1:1.5), continue ultrasonication for 30 minutes, then transfer the solution to a three-necked flask, heat it in a water bath at 80°C and stir for 2 hours to allow it to react fully. After the reaction is completed, take it out and wait for it to cool to room temperature, wash the CaIn2S4 / NiTiO3 1:1.5 product with deionized water and ethanol, and centrifuge it. Then, the product obtained by centrifugation and washing is vacuum dried at 60°C for 12 hours, ground into powder with a mortar, and finally ground to obtain a CaIn2S4 / NiTiO3 1:1.5 powder sample.
[0059] Take 1000 μL of 2 g / L K2Cr2O7 mother solution and add it to the reactor. Add 49 ml of deionized water and stir evenly. Take 4 ml as reference solution. Then weigh 20 mg of CaIn2S4 / NiTiO3 1:1.5 powder and put it into the reactor. Stir evenly and perform dark reaction for 30 min. After the dark reaction, take 4 mL of solution into a centrifuge tube. Then turn on the xenon lamp and take 4 mL of the mixed solution into the centrifuge tube every 10 min. Take 8 samples in total and centrifuge them with a centrifuge. Take the supernatant and test the UV-visible absorption spectrum of the hexavalent chromium residual solution with a UV-visible spectrophotometer. Figure 7As shown, the reduction rate of K2Cr2O7 obtained after 80 min of visible light irradiation is 90%. The curve conforms to the first-order kinetic law. The linear fitting is performed by taking the -In(C / C0) value of each reaction time point as the ordinate and the reaction time t as the abscissa to obtain the kinetic curve diagram ( Figure 8 ) The reduction rate of hexavalent chromium is 0.018 min -1 .
[0060] Example 4
[0061] The difference between this embodiment and embodiment 1 is that the mass ratio of the theoretical yield of calcium indium sulfide to the added nickel titanate is 5:1. The reduction rate of K2Cr2O7 obtained by the experiment in this embodiment is 80% when the sample is irradiated with visible light for 80 min. The reduction rate of hexavalent chromium is 0.020 min -1 .
[0062] Example 5
[0063] The difference between this embodiment and embodiment 1 is that the mass ratio of the theoretical yield of calcium indium sulfide to the added nickel titanate is 10:1. The reduction rate of K2Cr2O7 obtained by the experiment in this embodiment is 70% when the sample is irradiated with visible light for 80 min. The reduction rate of hexavalent chromium is 0.015 min -1 .
[0064] Example 6
[0065] The difference between this embodiment and embodiment 1 is that the pH of the solution is adjusted to 2. The reduction rate of K2Cr2O7 in this embodiment is 91% when the sample is irradiated with visible light for 80 min. The reduction rate of hexavalent chromium is 0.030 min -1 .
[0066] Example 7
[0067] The difference between this embodiment and embodiment 1 is that the pH of the solution is adjusted to 3. The reduction rate of K2Cr2O7 obtained by the experiment in this embodiment is 87% when the sample is irradiated with visible light for 80 min. The reduction rate of hexavalent chromium is 0.026 min -1 .
[0068] Example 8
[0069] The difference between this embodiment and embodiment 1 is that the water bath heating temperature is 60°C and the heating time is 3 h. The reduction rate of K2Cr2O7 obtained by the experiment in this embodiment is 75% when the visible light is irradiated for 80 min. The reduction rate of hexavalent chromium is 0.017min -1 .
[0070] Example 9
[0071] The difference between this embodiment and embodiment 1 is that the water bath heating temperature is 100°C and the heating time is 1 hour. The reduction rate of K2Cr2O7 obtained by the experiment in this embodiment is 80% when the visible light is irradiated for 80 minutes, and the reduction rate of hexavalent chromium is 0.020min -1 .
[0072] Example 10
[0073] The difference between this example and Example 1 is that the amount of glycerol used is 16 mL. The reduction rate of K2Cr2O7 obtained by the experiment in this example is 75% when the sample is irradiated with visible light for 80 min. The reduction rate of hexavalent chromium is 0.017 min -1 .
[0074] Embodiment 11
[0075] The difference between this example and Example 1 is that the amount of glycerol used is 4 mL. The reduction rate of K2Cr2O7 obtained by the experiment in this example is 92% when the sample is irradiated with visible light for 80 min. The reduction rate of hexavalent chromium is 0.031 min -1 .
[0076] Example 12
[0077] The difference between this embodiment and embodiment 1 is that 1.0 mmol of indium chloride tetrahydrate (InCl3•4H2O), 0.5 mmol of calcium chloride (CaCl2), 4.0 mmol of thioacetamide (C2H5N S ). The reduction rate of K2Cr2O7 in this example sample was 85% when irradiated with visible light for 80 min. The reduction rate of hexavalent chromium was 0.024 min -1 .
[0078] Embodiment 13
[0079] The difference between this embodiment and embodiment 1 is that 1.0 mmol of indium chloride tetrahydrate (InCl3•4H2O), 0.5 mmol of calcium chloride (CaCl2), 2.0 mmol of thioacetamide (C2H5N S ). The reduction rate of K2Cr2O7 in this example sample was 50% after 80 min of visible light irradiation. The reduction rate of hexavalent chromium was 0.009 min -1 .
[0080] Embodiment 14
[0081] The difference between this embodiment and embodiment 1 is that the precursor powder is heat treated at 400 °C for 2 h. The reduction rate of K2Cr2O7 obtained by the experiment in this embodiment is 80% when it is irradiated with visible light for 80 min. The reduction rate of hexavalent chromium is 0.020 min -1 .
[0082] Embodiment 15
[0083] The difference between this embodiment and embodiment 1 is that the precursor powder is heat treated at 700 °C for 2 h. The reduction rate of K2Cr2O7 obtained by the experiment in this embodiment is 60% when it is irradiated with visible light for 80 min. The reduction rate of hexavalent chromium is 0.011 min -1 .
[0084] Example 16
[0085] The difference between this embodiment and embodiment 1 is that 500 μL of 2 g / L K2Cr2O7 mother liquor is added to the reactor, 49.5 ml of deionized water is added, and stirred evenly to obtain a target pollutant aqueous solution. Under the conditions of this embodiment, the curve of the change of K2Cr2O7 solution concentration over time is obtained through experiments, as shown in FIG. Fig. 9 As shown, the reduction rate of K2Cr2O7 obtained after 80 min of visible light irradiation is 97.5%. The curve conforms to the first-order kinetic law. The linear fitting is performed by taking the -In(C / C0) value of each reaction time point as the ordinate and the reaction time t as the abscissa to obtain the kinetic curve diagram ( Fig. 9 ), the reduction rate of hexavalent chromium was obtained to be 0.067 min -1 .
[0086] Embodiment 17
[0087] The difference between this embodiment and embodiment 1 is that 1500 μL of 2 g / L K2Cr2O7 mother solution is added to the reactor, 48.5 ml of deionized water is added, and stirred evenly to obtain a target pollutant aqueous solution. Under the conditions of this embodiment, the curve of the change of K2Cr2O7 solution concentration over time is obtained through experiments, as shown in FIG. Fig. 9 As shown, the reduction rate of K2Cr2O7 obtained when the visible light was irradiated for 80min was 71%. The curve conforms to the first-order kinetic law. The linear fitting is performed by taking the -In(C / C0) value of each reaction time point as the ordinate and the reaction time t as the abscissa to obtain the kinetic curve diagram ( Fig.10 ), the reduction rate of hexavalent chromium is 0.013 min -1 .
[0088] Comparative Example 1 (nickel titanate as catalyst)
[0089] 5 mL of tetrabutyl titanate and 100 mL of ethylene glycol were mixed, and 2.48 g of nickel acetate tetrahydrate was added after thorough mixing. The reaction was stirred for 1 h, and then a light blue precipitate was obtained. Subsequently, the product was washed and centrifuged three times with deionized water and ethanol solution, and then the product was vacuum dried at 60 °C for 4 h, and finally ground to obtain a precursor powder, which was heat treated at 600 °C for 2 h to obtain nickel titanate nanorods.
[0090] Take 1000 μL of 2 g / L K2Cr2O7 mother liquor and add it to the reactor. Add 49 ml of deionized water and stir evenly. Take 4 ml as the reference solution. Then weigh 20 mg of nickel titanate powder and put it into the reactor. Stir evenly and perform dark reaction for 30 min. After the dark reaction, take 4 mL of solution into a centrifuge tube. Then turn on the xenon lamp and take 4 mL of the mixed solution into the centrifuge tube every 10 min. Take 8 samples in total and centrifuge them in a centrifuge. Take the supernatant and test the UV-visible absorption spectrum of the hexavalent chromium residual solution using a UV-visible spectrophotometer. Figure 7 As shown, the reduction rate of K2Cr2O7 was 0 when exposed to visible light for 80 min.
[0091] Comparative Example 2 (CaIn2S4 as catalyst)
[0092] Use a measuring cylinder to measure 32 ml of deionized water, adjust the pH of the solution to 2.5, and then use a measuring cylinder to measure 8 mL of glycerol and add it to the beaker. Stir for 10 min to completely mix the glycerol and water. Use a four-position balance to weigh 1.0 mmol of indium trichloride tetrahydrate (InCl3•4H2O), 0.5 mmol of calcium chloride (CaCl2), 3.0 mmol of thioacetamide (C2H5N S ). Continue stirring for 20 minutes until all the drugs are completely dissolved, then transfer the solution to a three-necked flask, heat it in a water bath at 80°C and stir it for 2 hours to allow it to react fully. After the reaction is completed, take it out and wait for it to cool to room temperature, wash the CaIn2S4 product with deionized water and ethanol, and centrifuge it. Then, dry the product obtained by centrifugation and washing in a vacuum at 60°C for 12 hours, grind it into powder with a mortar, and finally grind it to obtain a CaIn2S4 powder sample.
[0093] Take 1000 μL of 2 g / L K2Cr2O7 mother solution and add it to the reactor. Add 49 ml of deionized water and stir evenly. Take 4 ml as reference solution. Then weigh 20 mg of CaIn2S4 powder and put it into the reactor. Stir evenly and perform dark reaction for 30 min. After the dark reaction, take 4 mL of solution into a centrifuge tube. Then turn on the xenon lamp and take 4 mL of the mixed solution into the centrifuge tube every 10 min. Take 8 samples in total and centrifuge them in a centrifuge. Take the supernatant and test the UV-visible absorption spectrum of the hexavalent chromium residual solution using a UV-visible spectrophotometer. Figure 7 As shown in the figure, the reduction rate of K2Cr2O7 was 59% when it was irradiated with visible light for 80 min. The curve conforms to the first-order kinetic law. The linear fitting is performed by taking the -In(C / C0) value of each reaction time point as the ordinate and the reaction time t as the abscissa, and the reduction rate of hexavalent chromium is 0.010min -1 .
[0094] Comparative Example 3 (without catalyst)
[0095] Take 1000 μL of 2 g / L K2Cr2O7 mother solution and add it to the reactor. Add 49 ml of deionized water and stir evenly. Take 4 ml as reference solution. After stirring evenly, perform dark reaction for 30 min. After the dark reaction is finished, take 4 mL of solution into a centrifuge tube. Then turn on the xenon lamp and take 4 mL of the mixed solution into the centrifuge tube every 10 min. Take 8 samples in total and use a UV-visible spectrophotometer to test the UV-visible absorption spectrum of the hexavalent chromium residual solution. Figure 7 As shown, the reduction rate of K2Cr2O7 was 0 when exposed to visible light for 80 min.
[0096] Comparative Example 4 (No Light)
[0097] 5 mL of tetrabutyl titanate and 100 mL of ethylene glycol were mixed, and 2.48 g of nickel acetate tetrahydrate was added after thorough mixing. The reaction was stirred for 1 h, and then a light blue precipitate was obtained. Subsequently, the product was washed and centrifuged three times with deionized water and ethanol solution, and then the product was vacuum dried at 60 °C for 4 h, and finally ground to obtain a precursor powder, which was heat treated at 600 °C for 2 h to obtain nickel titanate nanorods.
[0098] Use a measuring cylinder to measure 32 ml of deionized water, adjust the pH of the solution to 2.5, and then use a measuring cylinder to measure 8 mL of glycerol and add it to the beaker. Stir for 10 min to completely mix the glycerol and water. Use a four-position balance to weigh 1.0 mmol of indium trichloride tetrahydrate (InCl3•4H2O), 0.5 mmol of calcium chloride (CaCl2), 3.0 mmol of thioacetamide (C2H5N S ). Continue stirring for 20 minutes until all the drugs are completely dissolved, accurately weigh nickel titanate nanorods according to the theoretical yield of 0.5 mmol indium calcium sulfide and add them to the reaction system (the product is marked as CaIn2S4 / NiTiO3 1:1), continue ultrasonication for 30 minutes, then transfer the solution to a three-necked flask, heat it in a water bath at 80°C and stir for 2 hours to allow it to react fully. After the reaction is completed, take it out and wait for it to cool to room temperature, wash the CaIn2S4 / NiTiO3 1:1 product with deionized water and ethanol, and centrifuge it. Then, the product obtained by centrifugation and washing is vacuum dried at 60°C for 12 hours, ground into powder with a mortar, and finally ground to obtain a CaIn2S4 / NiTiO3 1:1 powder sample.
[0099] Take 1000 μL of 2 g / L K2Cr2O7 mother solution and add it to the reactor. Add 49 ml of deionized water and stir evenly. Take 4 ml as the reference solution. Then weigh 20 mg of CaIn2S4 / NiTiO3 1:1 powder and put it into the reactor. Stir evenly and perform dark reaction for 30 min. After the dark reaction, take 4 mL of solution into a centrifuge tube and continue the reaction without light. Take 4 mL of the mixed solution into the centrifuge tube every 10 min. Take 8 samples in total and centrifuge them with a centrifuge. Take the supernatant and test the UV-visible absorption spectrum of the hexavalent chromium residual solution with a UV-visible spectrophotometer. Select the absorbance of the K2Cr2O7 solution at the maximum absorption wavelength of 258 nm to obtain the curve of the concentration of the K2Cr2O7 solution over time, as shown in Figure 1. Figure 7 As shown, the adsorption rate of K2Cr2O7 was 16% after 110 min of dark reaction.
[0100] Comparative Example 5 (Effect of pH)
[0101] 5 mL of tetrabutyl titanate and 100 mL of ethylene glycol were mixed, and 2.48 g of nickel acetate tetrahydrate was added after thorough mixing. The reaction was stirred for 1 h, and then a light blue precipitate was obtained. Subsequently, the product was washed and centrifuged three times with deionized water and ethanol solution, and then the product was vacuum dried at 60 °C for 4 h, and finally ground to obtain a precursor powder, which was heat treated at 600 °C for 2 h to obtain nickel titanate nanorods.
[0102] Use a measuring cylinder to measure 32 ml of deionized water, adjust the pH of the solution to 1, and then use a measuring cylinder to measure 8 mL of glycerol and add it to the beaker. Stir for 10 minutes to completely mix the glycerol and water. Use a four-position balance to weigh 1.0 mmol of indium trichloride tetrahydrate (InCl3•4H2O), 0.5 mmol of calcium chloride (CaCl2), 3.0 mmol of thioacetamide (C2H5N S ). Continue stirring for 20 minutes until all the drugs are completely dissolved, accurately weigh nickel titanate nanorods according to the theoretical yield of 0.5 mmol indium calcium sulfide and add them to the reaction system (the product is marked as CaIn2S4 / NiTiO3 1:1), continue ultrasonication for 30 minutes, then transfer the solution to a three-necked flask, heat it in a water bath at 80°C and stir for 2 hours to allow it to react fully. After the reaction is completed, take it out and wait for it to cool to room temperature, wash the CaIn2S4 / NiTiO3 1:1 product with deionized water and ethanol, and centrifuge it. Then, the product obtained by centrifugation and washing is vacuum dried at 60°C for 12 hours, ground into powder with a mortar, and finally ground to obtain a CaIn2S4 / NiTiO3 1:1 powder sample.
[0103] Take 1000 μL of 2 g / L K2Cr2O7 mother liquor and add it to the reactor. Add 49 ml of deionized water and stir evenly. Take 4 ml as the reference solution. Then weigh 20 mg of CaIn2S4 / NiTiO3 1:1 powder and put it into the reactor. Stir evenly and perform dark reaction for 30 min. After the dark reaction, take 4 mL of solution into a centrifuge tube and continue the reaction without light. Take 4 mL of the mixed solution into the centrifuge tube every 10 min. Take 8 samples in total and centrifuge them. Take the supernatant and use a UV-visible spectrophotometer to test the UV-visible absorption spectrum of the hexavalent chromium residual solution. Select the absorbance of the K2Cr2O7 solution at the maximum absorption wavelength of 258 nm to obtain the curve of the concentration of the K2Cr2O7 solution over time. The reduction rate of K2Cr2O7 at 80 min of light is 86%. The reduction rate of hexavalent chromium is 0.025 min -1 .
[0104] Comparative Example 6 (Effect of pH)
[0105] 5 mL of tetrabutyl titanate and 100 mL of ethylene glycol were mixed, and 2.48 g of nickel acetate tetrahydrate was added after thorough mixing. The reaction was stirred for 1 h, and then a light blue precipitate was obtained. Subsequently, the product was washed and centrifuged three times with deionized water and ethanol solution, and then the product was vacuum dried at 60 °C for 4 h, and finally ground to obtain a precursor powder, which was heat treated at 600 °C for 2 h to obtain nickel titanate nanorods.
[0106] Use a measuring cylinder to measure 32 ml of deionized water, adjust the pH of the solution to 4, and then use a measuring cylinder to measure 8 mL of glycerol and add it to the beaker. Stir for 10 minutes to completely mix the glycerol and water. Use a four-position balance to weigh 1.0 mmol of indium trichloride tetrahydrate (InCl3•4H2O), 0.5 mmol of calcium chloride (CaCl2), 3.0 mmol of thioacetamide (C2H5N S ). Continue stirring for 20 minutes until all the drugs are completely dissolved, accurately weigh nickel titanate nanorods according to the theoretical yield of 0.5 mmol indium calcium sulfide and add them to the reaction system (the product is marked as CaIn2S4 / NiTiO3 1:1), continue ultrasonication for 30 minutes, then transfer the solution to a three-necked flask, heat it in a water bath at 80°C and stir for 2 hours to allow it to react fully. After the reaction is completed, take it out and wait for it to cool to room temperature, wash the CaIn2S4 / NiTiO3 1:1 product with deionized water and ethanol, and centrifuge it. Then, the product obtained by centrifugation and washing is vacuum dried at 60°C for 12 hours, ground into powder with a mortar, and finally ground to obtain a CaIn2S4 / NiTiO3 1:1 powder sample.
[0107] Take 1000 μL of 2 g / L K2Cr2O7 mother liquor and add it to the reactor. Add 49 ml of deionized water and stir evenly. Take 4 ml as the reference solution. Then weigh 20 mg of CaIn2S4 / NiTiO3 1:1 powder and put it into the reactor. Stir evenly and perform dark reaction for 30 min. After the dark reaction, take 4 mL of solution into a centrifuge tube and continue the reaction without light. Take 4 mL of the mixed solution into the centrifuge tube every 10 min. Take 8 samples in total and centrifuge them. Take the supernatant and test the UV-visible absorption spectrum of the hexavalent chromium residual solution with a UV-visible spectrophotometer. Select the absorbance of the K2Cr2O7 solution at the maximum absorption wavelength of 258 nm to obtain the curve of the concentration of the K2Cr2O7 solution over time. The reduction rate of K2Cr2O7 at 80 min of light is 83%. The reduction rate of hexavalent chromium is 0.022 min -1 .
[0108] Comparative Example 7 (Effect of Glycerol)
[0109] 5 mL of tetrabutyl titanate and 100 mL of ethylene glycol were mixed, and 2.48 g of nickel acetate tetrahydrate was added after thorough mixing. The reaction was stirred for 1 h, and then a light blue precipitate was obtained. Subsequently, the product was washed and centrifuged three times with deionized water and ethanol solution, and then the product was vacuum dried at 60 °C for 4 h, and finally ground to obtain a precursor powder, which was heat treated at 600 °C for 2 h to obtain nickel titanate nanorods.
[0110] Use a measuring cylinder to measure 32 ml of deionized water and adjust the pH of the solution to 2.5. Use a four-position balance to weigh 1.0 mmol of indium chloride tetrahydrate (InCl3•4H2O), 0.5 mmol of calcium chloride (CaCl2), 3.0 mmol of thioacetamide (C2H5N S ). Continue stirring for 20 min until all the drugs are completely dissolved, accurately weigh nickel titanate nanorods according to the theoretical yield of 0.5 mmol indium calcium sulfide and add them to the reaction system (the product is marked as CaIn2S4 / NiTiO3 1:1), continue ultrasonication for 30 min, then transfer the solution to a three-necked flask, heat it in a water bath at 80°C and stir for 2 h to allow it to react fully. After the reaction is completed, take it out and wait for it to cool to room temperature, wash the CaIn2S4 / NiTiO3 1:1 product with deionized water and ethanol, and centrifuge it. Then, the product obtained by centrifugation and washing is vacuum dried at 60°C for 12 h, ground into powder with a mortar, and finally ground to obtain a CaIn2S4 / NiTiO3 1:1 powder sample.
[0111] Take 1000 μL of 2 g / L K2Cr2O7 mother liquor and add it to the reactor. Add 49 ml of deionized water and stir evenly. Take 4 ml as the reference solution. Then weigh 20 mg of CaIn2S4 / NiTiO3 1:1 powder and put it into the reactor. Stir evenly and perform dark reaction for 30 min. After the dark reaction, take 4 mL of solution into a centrifuge tube and continue the reaction without light. Take 4 mL of the mixed solution into the centrifuge tube every 10 min. Take 8 samples in total and centrifuge them. Take the supernatant and use a UV-visible spectrophotometer to test the UV-visible absorption spectrum of the hexavalent chromium residual solution. Select the absorbance of the K2Cr2O7 solution at the maximum absorption wavelength of 258 nm to obtain the curve of the concentration of the K2Cr2O7 solution over time. The reduction rate of K2Cr2O7 at 80 min of light is 85%. The reduction rate of hexavalent chromium is 0.024 min -1 .
[0112] Including but not limited to the above embodiments and comparative examples, zinc chloride or zinc sulfate of zinc salt, hydrated indium nitrate or indium chloride tetrahydrate of indium salt can be equally replaced in each embodiment without affecting the implementation effect, so each possible solution will not be listed here one by one.
[0113] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.
[0114] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. An application of an indium calcium sulfide-coated nickel titanate composite photocatalyst in the reduction of hexavalent chromium, wherein the application is carried out in an aqueous solution system, and the catalyst comprises nickel titanate nanorods and indium calcium sulfide nanosheets formed on the nickel titanate nanorods; The mass ratio of indium calcium sulfide nanosheets to nickel titanate nanorods is (0.5-10):
1.
2. The use of the calcium indium sulfide-coated nickel titanate composite photocatalyst in hexavalent chromium reduction according to claim 1, characterized in that: The calcium indium sulfide nanosheets are distributed on the nickel titanate nanorods in a randomly cross-linked form.
3. The use of the calcium indium sulfide-coated nickel titanate composite photocatalyst in the reduction of hexavalent chromium according to claim 2, characterized in that: The nickel titanate nanorods have a diameter of 300-400 nanometers and a length of 1-1.5 micrometers.
4. The use of the calcium indium sulfide-coated nickel titanate composite photocatalyst in hexavalent chromium reduction according to claim 1, characterized in that: The specific surface area of the catalyst is 65-75 m 2 / g.
5. Use of the calcium indium sulfide-coated nickel titanate composite photocatalyst in the reduction of hexavalent chromium according to any one of claims 1 to 4, characterized in that: The preparation method of the composite photocatalyst comprises: preparing nickel titanate nanorods; The nickel titanate nanorods are dispersed in water, and after adjusting the pH, a dispersant, a calcium salt, an indium salt, and a sulfiding agent are added and mixed evenly, and then reacted in a water bath and then separated.
6. The use of the calcium indium sulfide-coated nickel titanate composite photocatalyst in the reduction of hexavalent chromium according to claim 5, characterized in that: The molar ratio of the calcium salt, the indium salt and the sulfiding agent is 1:2:(4-8).
7. The use of the calcium indium sulfide coated nickel titanate composite photocatalyst in hexavalent chromium reduction according to claim 5, characterized in that: The volume ratio of the dispersant to water is (0-0.5):1, excluding 0.
8. The use of the calcium indium sulfide coated nickel titanate composite photocatalyst in hexavalent chromium reduction according to claim 5, characterized in that: The pH value is: 1-4, excluding the endpoint.
9. The use of the calcium indium sulfide-coated nickel titanate composite photocatalyst in the reduction of hexavalent chromium according to claim 5, characterized in that: The conditions of the water bath are: temperature of 60-100° C., and time of 1-3 h.
Citation Information
Patent Citations
Tungsten oxide nanorod / titanium carbide quantum dot / indium sulfide nanosheet Z-type heterojunction composite material and preparation method and application thereof
CN111974427A
Zero-dimensional cerium oxide / three-dimensional porous calcium indium sulfide composite nano material as well as preparation method and application thereof
CN114534745A